Microwave-Assisted Regioselective Synthesis and 2D-NMR Studies of New 1,2,3-Triazole Compounds Derived from Acridone - Mohammed Aarjane; Siham Slassi; Bouchra Tazi; Amina Amine (Journal of Chemistry)
A simple and mild protocol towards the synthesis of new 1,2,3-triazole compounds derived from acridone has been developed via regiospecific 1,3-dipolar cycloaddition reaction between 10-(prop-2-yn-1-yl)acridone derivatives and aromatic azides using CuI as a catalyst. The cycloaddition reaction has been performed using conventional as well as microwave-assisted methods. Microwave-assisted synthesis caused a significant reduction in the reaction times and improvement in the yields of all the synthesized compounds compared with the conventional method. The structure of the 1,4-disubstituted 1,2,3-triazoles has been elucidated by IR, HRMS, 1H-NMR, 13C-NMR, and 2D NMR (1H-13C HMBC, 1H-1H COSY, and 1H-1H NOESY) spectroscopies.